2021
DOI: 10.1136/bmjopen-2020-043897
|View full text |Cite
|
Sign up to set email alerts
|

Hospital staff, volunteers’ and patients’ perceptions of barriers and facilitators to communication following stroke in an acute and a rehabilitation private hospital ward: a qualitative description study

Abstract: ObjectivesTo explore barriers and facilitators to patient communication in an acute and rehabilitation ward setting from the perspectives of hospital staff, volunteers and patients following stroke.DesignA qualitative descriptive study as part of a larger study which aimed to develop and test a Communication Enhanced Environment model in an acute and a rehabilitation ward.SettingA metropolitan Australian private hospital.ParticipantsFocus groups with acute and rehabilitation doctors, nurses, allied health staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Literature has shown that a lack of communication has a negative effect on the rehabilitation process, as the personal needs of rehabilitants are unclear to the professionals ( 25 ). Good communication is complex and there can be multiple barriers and facilitators related to organization, staff, and rehabilitant factors ( 26 ). Barriers can, for example, relate to mixed wards, the power imbalance between staff and rehabilitants, staff perception of time pressures, personality, lack of knowledge and skills regarding communication, or a rehabilitant's functional and medical status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has shown that a lack of communication has a negative effect on the rehabilitation process, as the personal needs of rehabilitants are unclear to the professionals ( 25 ). Good communication is complex and there can be multiple barriers and facilitators related to organization, staff, and rehabilitant factors ( 26 ). Barriers can, for example, relate to mixed wards, the power imbalance between staff and rehabilitants, staff perception of time pressures, personality, lack of knowledge and skills regarding communication, or a rehabilitant's functional and medical status.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers can, for example, relate to mixed wards, the power imbalance between staff and rehabilitants, staff perception of time pressures, personality, lack of knowledge and skills regarding communication, or a rehabilitant's functional and medical status. Examples of facilitators are shared rooms, staff knowledge and utilization of communication strategies, and the personality of staff ( 26 ) This emphasizes the complexity and importance of communication, so rehabilitants know what to expect in a CRE and what they can do themselves. Therefore, when implementing a CRE, attention must be paid to all these aspects of communication.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to participate fully in communication is a severe challenge for PWA and HCPs and their ability to inform and involve patients. Being the second most frequent communication partner, only exceeded by family, the nursing staff play a vital role in the communicative rehabilitation post-stroke (D’Souza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%